PENGARUH RASIO AKTIVITAS, RASIO PROFITABILITAS, DAN RASIO PASAR TERHADAP RETURN SAHAM PERUSAHAAN SUB SEKTOR TELEKOMUNIKASI DI BURSA EFEK INDONESIA - Rosalina Pebrica Mayasari; Rika Anggraini (Program Studi Magister Manajemen FE Unsri, 2016)
This research performed in order to test the influence of activity ratio, profitability ratio and market ratio toward the stock return of sub-sector telecommunication companies that listed in Indonesia Stock Exchange for period 2011-2015. The sampling technique used in the research is purposive sampling with criteria as (1) listed in Indonesia Stock Exchange in 2011-2015. (2) always seem annual financial report over period 2011-2015). The sample of this research is six companies for five periods. Data analysis with multiple regressions with the ordinary least square (OLS) method. Hypotheses test used t-statistic and f-statistic at level significance 5%. The result of this research show Total Aset Turnover, Price Book Value, Price Earning Ratio have a significant effect on stock return. Besides, Working Capital Turnover, Return on asset and Return on Equity don’t have significant effect toward a stock return. Result of this research indicates that activity ratio, profitability ratio, and market ratio simultaneously have significant effect toward a stock return.